Urgensi Perlindungan Hak-hak Konsumen Dalam Transaksi Di E-Commerce - Abdul Halim Barkatullah (Fakultas Hukum Universitas Islam Indonesia, 2007)
The change of transaction method in business, which was previously real in character but change into virtual transaction, causing some new legal problems in trade transaction, particularly for consumer protection. Protection for consumer is needed because the consumers have not strong bargaining position. The legal protection of consumer’s rights in global e-commerce not only regulated by one legal aspect, but needs set of legal system which able to give simultaneous and comprehensive protection. Therefore, legal protection for consumer must be performed by using international approach through legal harmonisation dan cooperation between law officer intitutions.